2017
DOI: 10.1038/s41598-017-17389-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Reveals Cerebrospinal-Fluid Signatures of ALS

Abstract: Amyotrophic lateral sclerosis (ALS), the commonest adult-onset motor neuron disorder, is characterized by a survival span of only 2–5 years after onset. Relevant biomarkers or specific metabolic signatures would provide powerful tools for the management of ALS. The main objective of this study was to investigate the cerebrospinal fluid (CSF) lipidomic signature of ALS patients by mass spectrometry to evaluate the diagnostic and predictive values of the profile. We showed that ALS patients (n = 40) displayed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 32 publications
8
111
0
Order By: Relevance
“…The lipid profiling efforts in a SCA2 patient cerebellum and in spinocerebellar tissues from an authentic SCA2 mouse model showed deficits for very-long-chain C24 sphingomyelin as the main consistent finding in both organisms. A reduction of very-long-chain sphingomyelin was also observed in the CSF and blood of ALS patients, and this deficit correlated with lowest survival [128,129]. C24 sphingomyelin interacts with cholesterol in lipid bilayers, as important stabilizing elements for the plasma membrane particularly in myelinating glia cells [130,131].…”
Section: Discussionmentioning
confidence: 96%
“…The lipid profiling efforts in a SCA2 patient cerebellum and in spinocerebellar tissues from an authentic SCA2 mouse model showed deficits for very-long-chain C24 sphingomyelin as the main consistent finding in both organisms. A reduction of very-long-chain sphingomyelin was also observed in the CSF and blood of ALS patients, and this deficit correlated with lowest survival [128,129]. C24 sphingomyelin interacts with cholesterol in lipid bilayers, as important stabilizing elements for the plasma membrane particularly in myelinating glia cells [130,131].…”
Section: Discussionmentioning
confidence: 96%
“…Our observation concerning the drop in ν as N (CH 3 ) [19], assigned to choline group-component of the phosphatidylcholine and sphingomyelin, in ALS astrocytes together with the new analysis of the region around 1465 and 1377 cm −1 [40] (Figure 4D), point to a direct influence of these groups in lipid homeostasis in ALS astrocytes. Blasco and coworkers [51] highlighted phosphatidylcholine as a possible marker in the cerebrospinal fluid of ALS patients. For normal plasma membrane functionality and fluidity, lipid domains known as lipid rafts (mostly composed of sphingolipids and cholesterol) are crucial.…”
Section: F I G U R Ementioning
confidence: 99%
“…It has been shown that GAGs are involved in protein aggregation and prion diffusion ( [36][37][38][39][40][41][42][43][44] ). Lysosome activity changes were described in ALS caused by the C9orf72 gene repeat expansions ( [45][46][47][48][49] ), while synthesis of PA is linked to all types of phospholipids, including phosphatidylcholine and phosphatidylethanolamine that have been linked to ALS and prion disease pathogenesis ( 50,51 ).…”
Section: Functional Analysismentioning
confidence: 99%